Field notes contributed by Bill F. Huser, fall 1996 - Huser, Bill F.et al (1996)
List of birds and locations contributed by Bill F. Huser. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1996. Epson - sheet feed